FOREST RESOURCE MANAGEMENT DECISION MAKING BASED ON GENDER EQUALITY IN THE WAY BETUNG WATERSHED, LAMPUNG PROVINCE - Budiono, Pitojo; Erdian, Zeda; Wulandari, Christine; Puspasari, Eny; Syahiib, A. Nizam; Sari, Fadela Yunika; Apriliani, Adella Putri (Sosiohumaniora, 2024)
Environmental politics as part of social science has very broad aspects, one of which is the gender aspect. In fact, women can actively work in the public sector because it is important to balance gender roles between men and women. Cooperative decision making between men and women is a reflection of gender equality in forest resource management. This research analyzes the role of gender in decision making for forest resource management based on environmental politics in Pinang Jaya Village, Talang Mulya Village, and Cilimus Village around the Way Betung watershed. The data analysis used is descriptive quantitative. The research results show that gender roles in making decisions on forest resource management such as land preparation, seeding, planting, maintenance, harvesting and security activities are known to be dominated by husbands with an average percentage (77%), while women only dominate. in marketing activities with a percentage of (9%). The high role of men is caused by patriarchal cultural factors which still assume men have full access and good knowledge in managing forests. The correlation between job characteristics and decision making in forest resource management such as land preparation, seeding, planting, maintenance, harvesting, marketing and security is known to have a significant relationship. Meanwhile, there are still variables that are not correlated with the correlation between age, gender and education. Based on environmental political aspects, there is a need for intensive understanding and training regarding gender balance for site leaders because it has been proven that gender is correlated with the sustainability of natural resources.